2001
DOI: 10.1074/jbc.m007101200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-Ketoacyl-Acyl Carrier Protein Synthases by Thiolactomycin and Cerulenin

Abstract: H333N] was significantly more resistant to both antibiotics than FabB and had an affinity for TLM an order of magnitude less than the wild-type enzyme, illustrating that the two-histidine active site architecture is critical to protein-antibiotic interaction. These data provide a structural framework for understanding antibiotic sensitivity within this group of enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
380
0
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(425 citation statements)
references
References 55 publications
15
380
0
8
Order By: Relevance
“…6 As for C75 and cerulenin, two other known FAS inhibitors, it has been reported that they inhibit FAS by irreversibly binding to the the ketoacyl synthase of FAS, and that their inhibition of FAS is related to the binding site of the substrate Mal-CoA or Ac-CoA. 6,17,18 Therefore, as regards inhibition mechanism, GE is totally different from the other three inhibitors previously reported. In addition, GE can possibly affect other sites of FAS besides the ketoacyl reductase, because the IC 50 values for the overall reaction and ketoacyl reductase are not identical.…”
Section: Discussionmentioning
confidence: 72%
“…6 As for C75 and cerulenin, two other known FAS inhibitors, it has been reported that they inhibit FAS by irreversibly binding to the the ketoacyl synthase of FAS, and that their inhibition of FAS is related to the binding site of the substrate Mal-CoA or Ac-CoA. 6,17,18 Therefore, as regards inhibition mechanism, GE is totally different from the other three inhibitors previously reported. In addition, GE can possibly affect other sites of FAS besides the ketoacyl reductase, because the IC 50 values for the overall reaction and ketoacyl reductase are not identical.…”
Section: Discussionmentioning
confidence: 72%
“…By using this assay, we measured the condensation activity of KasA in the presence of various drugs. Activated INH did not inhibit KasA activity in vitro, whereas CER, a known inhibitor of ␤-ketoacyl-ACP synthases (34,64), inhibited the activity very efficiently. In contrast, and as reported by others (65), KatG-activated INH strongly inhibited InhA activity.…”
Section: Discussionmentioning
confidence: 99%
“…PctT is also highly homologous to ChlB3, ChlB6 [19], AviN [16], and CalO4 [17], all of which accompany with an iterative type I PKS. These homologous proteins were presumed to attach the starter unit, acetyl CoA, onto the corresponding PKSs, since FabH enzymes use an acyl-CoA rather than an acyl-ACP as the primer and catalyze the first condensation step in the pathway [55,56]. PctT is thus proposed to catalyze the priming reaction with acetyl CoA onto a discrete ACP PctK, which would be specifically recognized by an iterative type I PKS PctS for the formation of 6-MSA.…”
Section: Functional Analysis Of the Pctl Gene Encoding A Glycosyltranmentioning
confidence: 99%